Using tyrosinase as a tri-modality reporter gene to monitor transplanted stem cells in acute myocardial infarction - Mei Liu; Yichun Wang; Mengting Li; Hongyan Feng; Qingyao Liu; Chunxia Qin; Yongxue Zhang; Xiaoli Lan (Experimental and Molecular Medicine)
Abstract The study aimed to investigate the feasibility of noninvasive monitoring of bone marrow mesenchymal stem cells (MSCs) transduced with the tyrosinase reporter gene for acute myocardial infarction (AMI) with photoacoustic imaging (PAI), magnetic resonance imaging (MRI), and positron emission tomography (PET) in vitro and in vivo. MSCs were transduced with a lentivirus carrying a tyrosinase reporter gene. After transduction, the rate of 18F-5-fluoro-N-(2-[diethylamino]ethyl)picolinamide (18F-5-FPN) uptake was measured. PAI and MRI of stable cell lines expressing tyrosinase (TYR-MSCs) were performed in vitro. An AMI model was induced and verified. TYR-MSCs and MSCs were injected into the margins of the infarcted areas, and PAI, MRI, and PET images were acquired 1, 7, 14, 21, and 28 days after cell injection. Sham-operated models without injection were used as the control group. TYR-MSCs showed noticeably higher uptake of 18F-5-FPN and stronger signals in T1-weighted MRI and PAI than non-transduced MSCs. In vivo studies revealed prominent signals in the injected area of the infarcted myocardium on PAI/MRI/PET images, whereas no signal could be seen in rats injected with non-transduced MSCs or sham-operated rats. The uptake values of 18F-5-FPN in vivo showed a slight decrease over 28 days, whereas MRI and PAI signal intensity decreased dramatically. MSCs stably transduced with the tyrosinase reporter gene could be monitored in vivo in myocardial infarction models by PET, MRI, and PAI, providing a feasible and reliable method for checking the viability, location, and dwell time of transplanted stem cells.